The use of equivalent temperature to analyse climate variability - Ribera, P.; Gallego, D.; Gimeno, L.; Pérez Campos, J. F.; García Herrera, Ricardo Francisco; Hernández, E.; Torre, L. de la; Nieto, R.; Calvo Fernández, Natalia (Springer, 2004)
© 2004 StudiaGeo s.r.o. Equivalent temperature based in the NCEP/NCAR reanalysis database has been used as a simultaneous measure of temperature and humidity. Its variations during the 1958-1998 added to the effect of the inclusion of satellite data during the late seventies have been analyzed. An increase of the globally averaged equivalent temperature has been detected, the trend has been considerably greater during the first half of the study period and significant differences can be found between continental and oceanic areas. The relation of the trend with four of the main modes of climate variability has been assessed. The North Atlantic Oscillation and the Artic Oscillations are closely related to the equivalent temperature over the North Atlantic basin, extending toward Northern Asia in the second case. El Nino/Southern Oscillation and the Antarctic Oscillation seem to have a more global effect. Depto. de Física de la Tierra y Astrofísica Fac. de Ciencias Físicas TRUE pub